2021
DOI: 10.1371/journal.pone.0254118
|View full text |Cite
|
Sign up to set email alerts
|

A novel high-throughput screen for identifying lipids that stabilise membrane proteins in detergent based solution

Abstract: Membrane proteins have a range of crucial biological functions and are the target of about 60% of all prescribed drugs. For most studies, they need to be extracted out of the lipid-bilayer, e.g. by detergent solubilisation, leading to the loss of native lipids, which may disturb important protein-lipid/bilayer interactions and thus functional and structural integrity. Relipidation of membrane proteins has proven extremely successful for studying challenging targets, but the identification of suitable lipids ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…Our results above suggest the two structurally characterised mPPases induce an anionic lipid fingerprint in model membranes. As other mPPase studies have also indicated that lipid binding could be of interest for functional and stabilising studies [ 17 , 30 ], we modelled the Na + /H + -PPase from C . leptum ( Cp- PPase; see Methods for details) to examine whether the anionic lipid fingerprint is found in other members of this family.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results above suggest the two structurally characterised mPPases induce an anionic lipid fingerprint in model membranes. As other mPPase studies have also indicated that lipid binding could be of interest for functional and stabilising studies [ 17 , 30 ], we modelled the Na + /H + -PPase from C . leptum ( Cp- PPase; see Methods for details) to examine whether the anionic lipid fingerprint is found in other members of this family.…”
Section: Resultsmentioning
confidence: 99%
“…Our results above suggest the two structurally characterised mPPases induce an anionic lipid fingerprint in model membranes. As other mPPase studies have also indicated that lipid binding could be of interest for functional and stabilising studies [17,30], we modelled the Na + /H + -PPase from C. leptum (Cp-PPase; see Methods for details) to examine whether the anionic lipid fingerprint is found in other members of this family. Despite producing two high quality models from both Robetta and AlphaFold2 with significant similarity (1.05 Å RMSD), the Robetta homology model (reference PDB ID: 5GPJ) was chosen for this study as the arrangement of the distal helices was more in keeping with those seen in Tm-PPase and Vr-PPase structures (S10 Fig) . Clostridium species are predicted to contain POPG, POPE, POPS and cardiolipin, in addition to diradylglycerols.…”
Section: Homology-modelled Crystallography Target Cp-ppase Retains Th...mentioning
confidence: 99%
“…Maltosides such as dodecyl-maltoside (DDM) enable efficient extraction and yield functional protein making the maltoside class some of the most commonly used detergents in structural biology [ 38 ]. Hundreds more detergents have been developed to stabilise MPs further leading to HTP screens to identify the most useful [ 39 , 40 ]. Recently introduced detergents include the neopentyl glycols [ 41 ] and glyco-diosgenin (GDN) which along with digitonin account for around a third of single-particle cryo-EM (cryo-SPA) structures.…”
Section: Establishing a Purification Methodsmentioning
confidence: 99%
“…4,5,18,25 Recent progresses in the development of screening platforms facilitate the assessment of detergents and detergent-lipid combinations for stabilizing membrane proteins in the absence of biomembranes. 26,27 Although it is well-known that membrane protein activity varies between detergents and lipids, it is not well understood how one can rationally optimize the molecular structure of detergents. Today, widely applicable detergent selection rules help to narrow down the chemical space of the detergentome to be considered for screenings.…”
Section: Membrane Protein Puricationmentioning
confidence: 99%